2019
DOI: 10.5194/amt-12-1141-2019
|View full text |Cite
|
Sign up to set email alerts
|

Large-volume air sample system for measuring <sup>34</sup>S∕<sup>32</sup>S isotope ratio of carbonyl sulfide

Abstract: Abstract. Knowledge related to sulfur isotope ratios of carbonyl sulfide (OCS or COS), the most abundant atmospheric sulfur species, remains scarce. An earlier method developed for sulfur isotopic analysis for OCS using S+ fragmentation by an isotope ratio mass spectrometer is inapplicable for ambient air samples because of the large samples required (approx. 500 L of 500 pmol mol−1 OCS). To overcome this difficulty, herein we present a new sampling system for collecting approximately 10 nmol of OCS from ambie… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
27
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(38 citation statements)
references
References 38 publications
1
27
0
Order By: Relevance
“…Based on the similarity of atmospheric δ 34 S(OCS) at two sites (Israel and the Canary Islands), with values of 12.8 to 13.4‰, Angert et al (19) reported sulfur isotopic homogeneity of atmospheric OCS. However, differences between δ 34 S(OCS) of (10.5 ± 0.4)‰ at Yokohama and δ 34 S(OCS) of (13.2 ± 0.6)‰ obtained in Israel and the Canary Islands indicate that the atmospheric δ 34 S(OCS) values might not always be constant (21). In addition, several observations have shown variations in [OCS], such as terrestrial seasonality (2) and high level of [OCS] spatially distributed in the boreal summer above the Indo-Pacific region (22) or downwind of air masses from continental China (23).…”
Section: Significancementioning
confidence: 87%
See 2 more Smart Citations
“…Based on the similarity of atmospheric δ 34 S(OCS) at two sites (Israel and the Canary Islands), with values of 12.8 to 13.4‰, Angert et al (19) reported sulfur isotopic homogeneity of atmospheric OCS. However, differences between δ 34 S(OCS) of (10.5 ± 0.4)‰ at Yokohama and δ 34 S(OCS) of (13.2 ± 0.6)‰ obtained in Israel and the Canary Islands indicate that the atmospheric δ 34 S(OCS) values might not always be constant (21). In addition, several observations have shown variations in [OCS], such as terrestrial seasonality (2) and high level of [OCS] spatially distributed in the boreal summer above the Indo-Pacific region (22) or downwind of air masses from continental China (23).…”
Section: Significancementioning
confidence: 87%
“…Sampling and the corresponding measurements applied a method developed in our earlier works (20,21). Briefly, the system consisted of two parts: a large volume air sampling system and an online OCS purification system.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…10 Measurements of sulfur isotope ratios (δ 34 S) in COS may be used to track COS sources and thus reduce the uncertainties in their ux estimations. 12,22,23,24 However, the isotopic mass balance approach works best if the COS end-members are directly measured and have a signi cantly different isotopic signature. Previous δ 34 S measurements of atmospheric COS are scarce and there have been no direct measurements of two important components: the δ 34 S of oceanic COS emissions and, the isotopic fractionation of COS during plant uptake.…”
mentioning
confidence: 99%
“…As COS was proposed as a major greenhouse gas in the Archean, its role in the early Earth should be further investigated. Recent development of δ 34 S (and potentially Δ 33 S) analytical methods for ambient COS may provide additional isotopic constrains for such investigation in the future.…”
Section: Present‐day Sulfur Isotopic Anomaliesmentioning
confidence: 96%